Treatment of rectal leiomyoma by endoscopic resection - Silva, Rafael Denadai Pigozzi; Saad-Hossne, Rogério [UNESP]; Ferraz, Rafael Aliceda; Matsushita, Marcus de Medeiros; Falzoni, Roberto; Teixeira, Fábio Vieira [UNESP] (FapUNIFESP (SciELO), 2011)
Leiomyomas of the rectum are rare, with low reported incidence in literature. In most cases, patients are asymptomatic, and are often incidental endoscopic findings. The difficult distinction from leiomyosarcomas, associated with the possibility of recurrence, implies the absence of a standard treatment. Endoscopic resection, if well indicated, may be a therapeutic option. In this study, we report two cases of asymptomatic leiomyoma of the rectum in two patients, discovered incidentally during a routine colonoscopy, removed by conventional polypectomy and discuss its diagnostic and therapeutic aspects based on a literature review.
Keywords: Colonoscopy; Leiomyoma; Rectal neoplasm